Instrumen dan Institusi Internasional Dalam penegakan HAM - Dedy Nursamsi (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2015)
Human rights are believed to have universal values, which means that they know no boundaries and time space. The universal value of human rights is confirmed in international instruments which also contain international institutions as human rights monitoring and enforcement agencies. In addition, international instruments on human rights can take the form of international customs, general principles of law recognized by civilized nations (ius cogens), and judicial decisions and teachings of legal experts. The development of international instruments on human rights has made rapid progress under the United Nations, in the form of international agreements in the form of conventions, covenants, statutes and other international standards. In addition, there are declarations, proclamations, codes of ethics, rules of action, basic principles and recommendations. . Then as part of the world community, Indonesia has ratified several international instruments on human rights. Ratification is carried out through statutory regulations in the form of Laws (UU) and Presidential Decrees (Keppres). Until 2006, there were 6 international human rights instruments that had been ratified, and 17 ILO instruments related to labor rights.Keywords: HAM; International Institutions Abstrak:HAM dipercaya sebagai memiliki nilai universal, yang berarti tidak mengenal batas dan ruang waktu. Nilai universal HAM tersebut dikukuhkan dalam instrumen Internasional yang juga memuat institusi (lembaga) Internasional sebagai lembaga pengawas dan penegakan HAM. Selain itu, instrumen Internasional tentang HAM dapat berbentuk kebiasaan Internasional, prinsip umum hukum yang diakui bangsa beradab (ius cogens), dan keputusan yudisial serta ajaran para ahli hukum. Perkembangan instrumen Internasional tentang HAM, mengalami kemajuan yang pesat di bawah PBB, baik berupa perjanjian Internasional dalam bentuk konvensi, kovenan, statuta serta standar Internasional lainnya.Selain itu, terdapat deklarasi, proklamasi, kode etik, aturan bertindak, prinsip-prinsip dasar dan rekomendasi. Kemudian sebagai bagian masyarakat dunia, Indonesia telah meratifikasi beberapa instrumen Internasional tentang HAM. Ratifikasi dilakukan melalui peraturan perundang-undangan dalam bentuk Undang-undang (UU) dan Keputusan Presiden (Keppres). Sampai tahun 2006 terdapat 6 instrumen Internasional HAM yang telah diratifikasi, dan 17 instrumen ILO yang berkaitan dengan hak hak perburuhan.Kata Kunci: HAM; Institusi Internasional